Volumechange and strength characteristics of normal and high-strength mortars: effect of aggregate type and water-binder ratio. Issue 1 (1st January 2018) - Nahhab, Ali H.; Zahra, Ghaida Faeq A.
Abstract: This study investigated the impact of aggregate type on the volumechanges including drying shrinkage, autogenous shrinkage, and swelling for mortars made with different w/b ratios. The main properties including compressive and flexural strengths were also studied. For this purpose, three groups of mixes were prepared: two of them were prepared with 0.2 and 0.3 w/b ratios which were classified as high-strength mortars, and for comparison, a one group of normal-strength mortars was prepared with a 0.5 w/c ratio. Each group consisted of three mixes made with natural sand (NS), limestone aggregate (LA), or recycled concrete aggregate (RCA). Within each group, the LA mixes generally showed the lowest drying shrinkage and autogenous shrinkage regardless of the w/b ratio, while the greatest ones were observed for RCA mortars. The results also indicated that the group of mixes of the 0.2 w/b ratio gave the highest autogenous shrinkage.